Ցեղասպանությունը որպես XX-րդ դարի մարդկության դեմ ուղղված հանցագործություն - Գևորգյան, Տաթևիկ (ԱրՊՀ հրատ․)
Дата 24 апреля 1915 года занимает особое место не только в истории геноцида армян, но и в истории армянского народа в целом. Османскими турками было совершено самое страшное преступление в истории человечества, в результате которого все армянское население было преднамеренно уничтожено на территории его исторической родины. С тех пор прошло 100 лет. Можем с гордостью заявить, что сделано не мало шагов, пройдено немало трудных путей для признания армянского геноцида. Но мы все понимаем, что этого недостаточно. Нужно делать все, чтобы Турция признала свою вину и возместила материальный и моральный ущерб… April 24, 1915 holds a special place not only in the history of the Armenian Genocide but also in the history of the Armenian nation as a whole. Ottoman Turks committed the most horrific crime in human history, as a result of which the entire Armenian population was deliberately destroyed on the territory of its historical homeland. 100 years have passed since then. We can proudly say that we have taken many steps towards recognition of the Armenian Genocide, while completing many difficult paths in our efforts. However we all understand that this is not enough. We need to endeavour every option so that Turkey admits its guilt and compensates moral and material losses.
Keywords: Արցախ; Հայոց ցեղասպանություն